Pseudoaneurysm of pulmonary artery: rare complication of systemic chemotherapy - Garg, Shivani (Clin Case Rep, 2015)
Pulmonary artery pseudoaneurysm is an uncommon yet fatal clinical entity. Its presentation can mimic a number of common diseases and can be easily missed. As pseudoaneurysm is associated with a number of fatal complications, clinicians should be aware of imaging features which distinguishes pseudoaneurysms from its close differentials. Early recognition and treatment of pseudoaneurysm can prevent fatal outcomes including hemothorax, rupture, or death.